Fatty Acid Increases cAMP-dependent Lactate and MAO-B-dependent GABA Production in Mouse Astrocytes by Activating a G(alpha s) Protein-coupled Receptor - Lee, NaHye; Sa, Moonsun; Hong, Yu Ri; Lee, C. Justin; Koo, JaeHyung (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2018)
Medium-chain fatty acids (MCFAs) are mostly generated from dietary triglycerides and can penetrate the blood-brain barrier. Astrocytes in the brain use MCFAs as an alternative energy source. In addition, MCFAs have various regulatory and signaling functions in astrocytes. However, it is unclear how astrocytes sense and take up MCFAs. This study demonstrates that decanoic acid (DA; C10), a saturated MCFA and a ligand of G(alpha s) protein-coupled receptors (G(alpha s)-GPCRs), is a signaling molecule in energy metabolism in primary astrocytes. cAMP synthesis and lactate release were increased via a putative G(alpha s)-GPCR and transmembrane adenylyl cyclase upon short-term treatment with DA. By contrast, monoamine oxidase B-dependent gamma-aminobutyric acid (GABA) synthesis was increased in primary cortical and hypothalamic astrocytes upon long-term treatment with DA. Thus, astrocytes respond to DA by synthesizing cAMP and releasing lactate upon short-term treatment, and by synthesizing and releasing GABA upon long-term treatment, similar to reactive astrocytes. Our data suggest that astrocytes in the brain play crucial roles in lipid-sensing via GPCRs and modulate neuronal metabolism or activity by releasing lactate via astrocyte-neuron lactate shuttle or GABA to influence neighboring neurons.
Keywords: REACTIVE ASTROCYTES; GLUCOSE-UTILIZATION; LIPID-ACCUMULATION; ENERGY-METABOLISM; ADENYLYL-CYCLASE; GLIAL-CELLS; IN-VITRO; BRAIN; NEURONS; DIET